2021
DOI: 10.1016/j.amsu.2021.102287
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of erythropoietin for wound healing: A systematic review of the literature

Abstract: Objectives To systematically review the available literature on the efficacy of erythropoietin for wound healing in human patients. Design The review was reported following Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. A descriptive-analytical method was used to analyse and integrate review findings. Data sources A primary search of electronic databases was performed using a combination of search terms related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…EPO, a glycosylated cytokine produced by peritubular cells in the kidneys as a treatment of anemia, has attracted increasing attention to be a potentially beneficial cytokine in wound healing. [211][212][213] Animal experiments identified that EPO could promote the release of growth factors such as VEGF, FGF, and insulin-like growth factor, 214 suppress the inflammatory responses and apoptosis, [215][216][217] stimulate angiogenesis, 218,219 promote the differentiation of myofibroblasts, 220 and orchestrate the remodeling of ECM. 221 To date, there are three RCTs 68,69,222 and one case series 223 that investigated the effect of EPO on diabetic ulcers either by topical or subcutaneous administration.…”
Section: Cytokine Based Therapymentioning
confidence: 99%
“…EPO, a glycosylated cytokine produced by peritubular cells in the kidneys as a treatment of anemia, has attracted increasing attention to be a potentially beneficial cytokine in wound healing. [211][212][213] Animal experiments identified that EPO could promote the release of growth factors such as VEGF, FGF, and insulin-like growth factor, 214 suppress the inflammatory responses and apoptosis, [215][216][217] stimulate angiogenesis, 218,219 promote the differentiation of myofibroblasts, 220 and orchestrate the remodeling of ECM. 221 To date, there are three RCTs 68,69,222 and one case series 223 that investigated the effect of EPO on diabetic ulcers either by topical or subcutaneous administration.…”
Section: Cytokine Based Therapymentioning
confidence: 99%
“…The global EPO drugs market size has already reached 12 billion USD and is estimated to grow at a compound annual growth rate (CAGR) of 10%, according to the Market Data Forecast. Other EPO-based therapeutic applications are under development, including prevention of dementia, Alzheimer’s disease, Parkinson’s disease, schizophrenia, bipolar disorder, depression, ischemic stroke, traumatic brain injury, diabetes mellitus, acute and chronic lung diseases, various ocular diseases, severe COVID-19, as well as EPO use in the regenerative medicine [ 1 , 3 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, the clinical use of the EPO-based medicines is limited due to the pleiotropic nature of this cytokine, leading to serious adverse reactions, such as arterial hypertension, cerebral convulsion/hypertensive encephalopathy, thrombo-embolism, iron deficiency, development of pure red cell aplasia, and the possibility of cancer progression [ 8 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%